Respuesta :

answer: 5

step by step:
okay so to do this you plug in 2 for x
g(2)=3(2)-1

then multiply 3 by 2
3*2=6

that makes g(2)=6-1

6-1=5

g(2)=5

Answer:

The value of g(2) would be 5.

Step-by-step explanation:

Here, the given function,

[tex]g(x) = 3x - 1[/tex],

By substituting x = 2 in the above equation,

We get,

[tex]g(2) = 3(2) - 1[/tex]

[tex]g(2) = 6 - 1[/tex]  ( By multiplication )

[tex]g(2) = 5[/tex]       ( by subtraction )

Hence, the value of g(2) would be 5.

ACCESS MORE